The Effect of The STAD Learning Model Aided by Students Worksheet to Improve Critical Thinking Skills of Students (Journal of Primary Education, 2020)
This study aims to determine the ability of critical thinking skills of students before and after the implementation of STAD learning models assisted by Students worksheet to analyze the effect of STAD learning models assisted by Students worksheet (LKPD) on critical thinking skills. This study was Quasi-experimental research. The population of this study was grade IV students of Diponegoro Cluster in Brebes District consisting of 203 students. Samples were taken by random sampling technique, a total of 60 students. The data of this study were obtained from tests and observations. Data were analysed using t-test analysis. The results showed that there was an increase in critical thinking skills before and after the implementation of the STAD learning model assisted by Students worksheet with a score of 10.55 and Sig, of 0.000. There is an effect of the STAD Learning Model by Students worksheet on students' critical thinking skills with at value of 7.18 and a Sig of 0.000. It can be concluded that there is a positif influence of the ability of students to think critically, before and after the STAD learning. The worksheet-assisted STAD learning models can improve critical thinking skills of students significantly.